On site, in sound : performance geographies in América Latina - Dorr, Kirstie A., 1972- (Refiguring American music., 2018)
Focusing on the hemispheric circulation of South American musical cultures, Kirstie A. Dorr examines the spatiality of sound and the ways in which the sonic is bound to perceptions and constructions of geographic space, showing how people can use music and sound to challenge and transform dominant conceptions of place.